Does feeling different from neighbors matter? Exploring the impact of perceived neighborhood environment on subjective well-being in a comprehensive framework - Hu, Yuchen; Zhang, Min; Chang, Enyu; Chen, Peipei; Jiao, Linshen (Social science & medicine (1982), 2026)
Neighborhood environments are seen as a crucial factor influencing residents’ subjective well-being (SWB). Current research suggests that the perceived neighborhood environment (PNE) exerts a stronger influence on SWB than the objective environment. However, there are two critical gaps in the literature. Firstly, the dimensions of PNE have not been sufficiently explored, especially horizontal social comparisons such as perceived neighborhood heterogeneity. Secondly, the pathways linking PNE to SWB have not been adequately investigated. These oversights lead to biased results and an incomplete understanding of the PNE-SWB relationship, and this study bridges the gaps by developing a more comprehensive research framework. Drawing on Nanjing PNE and SWB survey data, it shows firstly that after considering horizontal social comparisons within neighborhoods, the perceived neighborhood heterogeneity is a negative factor for SWB in the Chinese context, and secondly that the new framework shows how PNE influences SWB through distinct mediating pathways. Residential well-being mediates the relationship between the perceived neighborhood built environment and SWB, while activities are strongly influenced by perceived neighborhood lifestyle consistency, subsequently affecting SWB. Thirdly, we observed variations in paths of influence among groups with different health conditions, educational and income levels and hukou status. The study provides a deeper understanding of the relationship between PNE and SWB, offering theoretical support for human-oriented neighborhood planning practices. •We built a comprehensive framework to explain the mechanism from PNE to SWB.•Perceived neighborhood heterogeneity has a negative association with SWB.•We found potential mediating pathways between PNE and SWB.•Different groups exhibit distinct pathways from PNE to SWB.